2010
DOI: 10.3892/etm.2010.127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor angiogenesis by oral etoposide

Abstract: Abstract. the chemotherapeutic agent etoposide is a topoisomerase ii inhibitor widely used for cancer therapy. low-dose oral etoposide, administered at close regular intervals, has potent anti-tumor activity in patients who are refractory to intravenous etoposide; however, the mechanism remains unclear. Since endothelial cells may be more sensitive than tumor cells to chemotherapy agents, we determined the effects of etoposide alone and in combination with oral cyclooxygenase-2 inhibitors and peroxisome-prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Coussens et al described, in a seminal publication, a genetically engineered mouse model demonstrating inflammation is critical for carcinogenesis (38). We have previously demonstrated that anti-inflammatory drugs such as PPAR ligands and COX-2 inhibitors can inhibit tumor growth by suppressing inflammation and angiogenesis (39-43). …”
Section: Inflammation In Cancermentioning
confidence: 99%
“…Coussens et al described, in a seminal publication, a genetically engineered mouse model demonstrating inflammation is critical for carcinogenesis (38). We have previously demonstrated that anti-inflammatory drugs such as PPAR ligands and COX-2 inhibitors can inhibit tumor growth by suppressing inflammation and angiogenesis (39-43). …”
Section: Inflammation In Cancermentioning
confidence: 99%
“…[30] Thus, addition of celecoxib may remarkably increase the drug sensitivity of CCa cells to chemotherapy drugs like cyclophosphamide [30] and etoposide. [31] Our patient may have achieved long-term remission through this mechanism. The anticancer agent etoposide was added, keeping in mind the fact that oral etoposide has already been used in palliative regimens in various adult and pediatric solid tumors.…”
Section: Discussionmentioning
confidence: 90%
“…The anticancer agent etoposide was added, keeping in mind the fact that oral etoposide has already been used in palliative regimens in various adult and pediatric solid tumors. [31] Etoposide is also antiangiogenic and is synergestic when given with celecoxib. [31] Also, as many CCa patients may have abnormal liver function tests (LFTs), etoposide would be a relatively safer drug to be given in such settings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This tumor has been shown to express vascular endothelial growth factor receptor 2 [20]. Celecoxib [21] and etoposide [22,23] are shown to have an effect on medulloblastoma in vitro and in mice. Thalidomide has not been used in murine medulloblastoma studies due to its different metabolism in mice.…”
Section: Discussionmentioning
confidence: 98%